Zooplankton monitoring using a twin NORPAC net during the 59th Japanese Antarctic Research Expedition in austral summer 2017–2018 (National Institute of Polar Research, 2020)
As part of the monitoring program of the Japanese Antarctic Research Expedition (JARE), zooplankton sampling using a NORPAC (NORth PACific) standard net has been routinely carried out since JARE-14 (1972/73 season) to estimate the long-term trends of abundance, species composition and their temporal/spatial variation in the uppermost 150 m of the Indian Ocean sector of the Southern Ocean. Two separate monitoring surveys were completed during JARE-59 (December 2017 to March 2018). The icebreaker Shirase has a fixed schedule and route, traveling down longitude 110oE each December and returning along 150oE each March. Data collected on these fixed schedule seems to be ideal for long-term monitoring work in this region. We present data from its 2017/2018 voyage. In additions, separate samplings were carried out on board the T/V Umitaka-maru along 110oE longitude in January 2018. This report provides the latest zooplankton data. These transect data can be used as time series and/or seasonal sets over the last 45 years.